Analysis of IoT Design for Monitoring Electrical Energy Use in Homes - Afandi, Reza; Satria, Beni; Aryza , Solly (Cattleya Darmaya Fortuna, 2025)
The need for electrical energy efficiency is increasing along with the high cost of energy and concerns about environmental impacts. At the household scale, electrical energy waste often occurs due to the lack of effective monitoring. Internet of Things (IoT) technology offers an innovative solution by enabling real-time monitoring of energy consumption through connected devices. This study aims to design and implement an IoT system based on NodeMCU ESP32 and PZEM-004T sensor to monitor electrical energy usage in households. The research method involves the integration of current and voltage sensors with an ESP32 microcontroller, which is connected via a Wi-Fi network for data collection. The data collected includes electrical parameters such as voltage, current, power, and energy, which are then displayed in real-time through a user interface. The results show that this system is able to monitor energy consumption with good accuracy, detect energy waste patterns, and provide early warnings of electricity usage anomalies. This system also increases user awareness of energy consumption, thereby reducing electricity waste and supporting energy conservation efforts. Thus, this study contributes to the development of IoT technology for more efficient and sustainable household energy management.